2020
DOI: 10.1111/epi.16569
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral phenotypes of childhood idiopathic epilepsies

Abstract: ObjectiveTo characterize the presence and nature of discrete behavioral phenotypes and their correlates in a cohort of youth with new and recent onset focal and generalized epilepsies.MethodsThe parents of 290 youth (age = 8‐18 years) with epilepsy (n = 183) and typically developing participants (n = 107) completed the Child Behavior Checklist for children aged 6‐18 from the Achenbach System of Empirically Based Assessment. The eight behavior problem scales were subjected to hierarchical clustering analytics t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 38 publications
2
21
0
1
Order By: Relevance
“…Neuroimaging research has shown concomitant abnormalities consistent with the presence and degree of impairment across the cognitive phenotypes reflected in brain structure, connectivity (diffusion and resting state fMRI), and large‐scale covariance analyses of cortical/subcortical gray and white matter—the findings overall consistent with the hypothesis that disrupted networks rather than focal pathology primarily underlie the heterogeneous cognitive presentations of TLE 11,15‐18 …”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…Neuroimaging research has shown concomitant abnormalities consistent with the presence and degree of impairment across the cognitive phenotypes reflected in brain structure, connectivity (diffusion and resting state fMRI), and large‐scale covariance analyses of cortical/subcortical gray and white matter—the findings overall consistent with the hypothesis that disrupted networks rather than focal pathology primarily underlie the heterogeneous cognitive presentations of TLE 11,15‐18 …”
Section: Introductionmentioning
confidence: 58%
“…In the larger epilepsy neurobehavioral phenotype literature, the patterns shown here have been observed in cross-sectional and/or prospective investigations of quality of life, 43,44 cognitive trajectories of children treated surgically or medically, 45 and most patterns of depression in mothers of children with new onset epilepsy. 46 Cognitive phenotype investigations of adults with temporal lobe epilepsy have more typically identified varying patterns of abnormality across groups 10,9,17,11,13,14,16 as well as in patterns of executive function in children with epilepsy (Modi et al, 2019). That said, as this is the first attempt to characterize behavioral phenotype groups in temporal lobe epilepsy, more research is needed using other behavioral metrics and extension to other epilepsy syndromes to derive a fuller understanding of the taxonomy of behavioral abnormality in epilepsy and its associated patterns.…”
Section: Behavioral Phenotypesmentioning
confidence: 99%
See 3 more Smart Citations